Intensified reactive distillation configurations for production of dimethyl ether - Gor, Nikhil K.; Mali, Nilesh A.; Joshi, Sunil S. (Chemical Engineering and Processing-Process Intensification, 2020)
The combustion properties of dimethyl ether (DME) are similar to the conventional fuels; hence it is being used as a promising green energy source. The conventional method of DME production by methanol dehydration is highly energy consuming due to the use of a series of distillation columns. In the present study, an energy efficient reactive distillation configuration is proposed for DME production which leads to higher methanol conversion with less energy requirement as compared to reported configurations. The reactive distillation (RD) and dual reaction zone reactive divided wall column (RDWC) were analyzed using steady state ASPEN simulations. Subsequently, all the design parameters were optimized by sensitivity analysis to minimize the Total Annual Cost (TAC) of the configuration. The results showed that the RD column is more energy efficient than RDWC as it requires 10.68 % less TAC. The proposed RD and dual reaction zone RDWC configurations were found to have less specific energy requirements and less cost per kg of DME than any other configuration reported earlier.
Keywords: Energy efficient configuration; Reactive distillation; Reactive divided wall column; Total annual cost